How balance training on different types of surfaces effect dynamic balance ability and postural sway of gymnast children? - Gonener, Utku; Gonener, Ahmet (Progress in Nutrition, 2020)
Study Objectives: This study aimed to examine the impact of balance training performed on stable and unstable surfaces on the dynamic balance of children. Methods: The sample of the study consisted of 40 female gymnasts (7 years old). The sample was randomly divided into two groups and the first group (122.85±1.14 cm in height, 24.05±1.04 kg in weight) performed unstable surface training while the other group (123.92±1.33 cm in height, 24.95±1.36 kg in weight) performed stable surface training. Eight-week balance training programs were administered three days a week for 40 minutes a day. The pre and post-dynamic balances of the participants were measured with the Tecno-body ProKin PK200 model dynamic balance device. ML, PL, AGP, MS, and AP parameters were assessed, and comparisons were made by the paired t test in SPSS 17.00 package program. Results: While there was a statistically significant difference in all parameters, except for ML values, in the group who performed the balance training on an unstable surface (p 0.05). Conclusion: The results showed that training on unstable surface effect dynamic balance and postural sway in a positive way.